Prevalence of Helicobacter pylori in patients with different renal function - Rukiye VARDAR,; Enver VARDAR,; Hüsniye BOZDAĞ,; Baki GÜRGEN,; Hakan POSTACI,; Onur ÖZGENÇ, (Turkish Journal of Gastroenterology, 2019)
-